Floor Management Systems in an Organic Apple Orchard Affect Fruit Quality and Storage Life - Tahir, Ibrahim I.; Svensson, Sven-Erik; Hansson, David (HortScience, 2015)
In an organic apple orchard, standard mechanical cultivation was compared with four different orchard floor management systems (OFMS): acetic acid (V), living mulch (L), a sandwich system during the growing season (SSS), and a sandwich system during the whole year (SSW). The effects of these OFMS on weed management, soil conditions, tree growth, tree yield, fruit quality, and fruit storage potential in a cool climate were evaluated. Acetic acid treatment showed good weed suppression without any amendatory effect on soil conditions, fruit quality, or tree performance. The L and SSS systems increased soil respiration, decreased tree vigor, and improved fruit quality, but had no sufficient influence on weed competition and thus decreased fruit yield. Only SSW gave better weed control, higher soil respiration, and acceptable tree growth with no yield reduction. Fruit from this system also showed better quality at harvest than fruit from other OFMS and maintained this good quality during storage. A 6-week weed-free period from late May to mid-July gave the highest apple yield in two OFMS (SSW and V).